Cohesion teams and working environment perceived by university employees Montemorelos - Paredes Saavedra, Maribel (2013)
This research sought to answer the question: Is there a relationship between the degree of cohesion of the teams and the quality level of the work environment perceived by employees of the University of Montemorelos, Nuevo Leon, Mexico? The research was a quantitative, descriptive, correlational, and cross country. The population consisted of 334 employees, of which a sample of 211. To collect data two instruments were developed: the first aimed at measuring the cohesion of teams and the second focused on measuring the perceived work environment, comprised of 20 items each. As a result it was observed that there is a significant positive linear relationship stronger grade between the variable cohesive work teams (CET) and the variable labor climate (CL). When running the test statistic r value was found to .803 and a significance level of .000 p. The results of the investigation showed that there is a significant positive linear relationship stronger grade between the variable cohesion of teams (CET) and the variable labor climate (CL). The study also showed a good degree of perceived cohesion of teams according to the levels used in the Likert scale and grade good quality working environment perceived as the levels used in the Likert scale.